PENGETAHUAN PAJAK, PERSEPSI, MOTIVASI DAN MINAT PAJAK PADA MAHASISWA - Ramadhan, Gilang Restu; Chotidjah, Erna; Okfitasari, Antin (ITB AAS Indonesia Surakarta, 2024)
The purpose of this study was to find out about the influence of tax knowledge, perceptions and motivation on tax interest of students who have taken taxation courses at universities in the city of Surakarta. The number of tax officials who have decreased has created opportunities for students who wish to have a career in taxation. In forming their interest in the field of taxation is usually determined by the knowledge of taxes obtained, then the perception and motivation. This research is a type of quantitative research with a descriptive approach. This study uses data processing with the Multiple Linear Regression Analysis method. The subjects in this study were students. The population and sample in this study are students who have taken taxation courses at universities in the city of Surakarta. The sample collection used a purposive sampling technique and a total of 109 questionnaire data were obtained which were processed using SPSS v23. The results showed that tax knowledge had a significant negative effect on student tax interest, perception had a significant positive effect on student tax interest and motivation had a non significant positive effect on student tax interest.